2021
DOI: 10.1016/j.apsb.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide YD attenuates inflammation via miR-155 targeting CASP12 during liver fibrosis

Abstract: The antimicrobial peptide APKGVQGPNG (named YD), a natural peptide originating from Bacillus amyloliquefaciens CBSYD1, exhibited excellent antibacterial and antioxidant properties in vitro . These characteristics are closely related to inflammatory responses which is the central trigger for liver fibrosis. However, the therapeutic effects of YD against hepatic fibrosis and the underlying mechanisms are rarely studied. In this study, we show that YD improved liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Correspondingly, we investigated the expressions of α-SMA and Collagen I. Immunostaining showed that the α-SMA and Collagen I expressions were significantly higher in the CCl 4 group than the solvent control group. Our results were in agreement with the findings of Yan et al ( Yan et al, 2021 ). This indicates that CCl 4 is able to promote the activation of HSCs as well as the accumulation of ECM.…”
Section: Discussionsupporting
confidence: 94%
“…Correspondingly, we investigated the expressions of α-SMA and Collagen I. Immunostaining showed that the α-SMA and Collagen I expressions were significantly higher in the CCl 4 group than the solvent control group. Our results were in agreement with the findings of Yan et al ( Yan et al, 2021 ). This indicates that CCl 4 is able to promote the activation of HSCs as well as the accumulation of ECM.…”
Section: Discussionsupporting
confidence: 94%
“…Experimental studies revealed that LL-37 [ 299 ] and S100 peptide [ 300 ] in keloid tissues mitigated collagen production, supporting the AMPs’ antifibrogenic properties. Yan et al [ 301 ] recently reported that the anti-fibrotic properties of AMP YD were mediated through the miR-155/Casp12/NF-kB pathway. In addition, the recombinant LL-37 can induce endothelial cell proliferation, migration and formation of tubule-like structures, and increase vascularization and re-epithelialization in mouse trauma experiments [ 302 ].…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…Liver fibrosis serves as a crucial pathological stage in the progression of liver cancer. Despite the promising outcomes observed in preclinical investigations, the effectiveness of antifibrotic candidates in clinical trials is limited [ 5 , 6 , 7 , 34 ]. Thus, more potential targets for the development of anti-liver-fibrosis therapeutics with thoroughly explained molecular mechanisms are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…If uncontrolled, liver fibrosis gradually progresses to liver cirrhosis and even hepatocellular carcinoma (HCC), ultimately leading to organ dysfunction and mortality and seriously threatening human health [ 2 , 3 , 4 ]. Unfortunately, there is still a lack of effective medical therapies for the treatment of liver fibrosis [ 5 , 6 , 7 ]. Thus, an in-depth understanding of the molecular basis of liver fibrosis is important and necessary for supporting the development of novel antifibrotic therapies.…”
Section: Introductionmentioning
confidence: 99%